Factors associated with health service utilization by rural elderly people in mainland China - LI, Rui (KDI School, 2015)
This study aims to describe the present situation of utilization for elderly in rural areas, and the factors significantly affecting health services utilization. Using descriptive analysis, Chi-square test, single-factor regression and multiple regression to find significantly associated factors influencing use of health services by rural elderly. Objective: Population aging has become the most important issue in many countries, especially in China. The purposes of this study to find the factors associated with health services utilization and determine the factors which significantly associated with using health services by rural elderly people in mainland China. Provide the policy proposals for improving health services utilization by rural elderly people in the future. Data and Methods: 1. Source of data: The data came from the China Rural Health Development Project included 40 rural counties in 8 provinces, which involved about 36,000 households (population around 110,000). 2. Methods: Logistic regression analysis is used in order to find the factors significantly associated to health services utilization. Results: Age, education, income, health self-appraisal, medical insurance, inhabitancy, health services provide by different health institutions can impact health services utility, health self-appraisal, health insurance and health institutions are most important factors. Chronic diseases is major diseases affected the health of elderly people in rural, the major reason of low treatment rate was financial difficulty. Conclusion: This study shows that major factors associated with health service utilization by rural elderly people include: region, age, income, health insurance, receipt of medical assistance, chronic diseases, need for care, and self-reported health status. There are large demand of long-term care because of more and more disabilities and handicaps rural elderly people. Government should improve the medical insurance system of rural elderly people, explore long-term care mechanisms, and clarify responsibilities of different level of health institutions to meet rural elderly people''s demand, improve household care for elderly.
Thesis(Master) --KDI School:Master of Public Policy,2015